2020
DOI: 10.1021/acsinfecdis.0c00560
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a Thio Functional Group to Diazabicyclooctane: An Effective Modification to Potentiate the Activity of β-Lactams against Gram-Negative Bacteria Producing Class A, C, and D Serine β-Lactamases

Abstract: By the emergence and worldwide spread of multi-drug-resistant Gram-negative bacteria, there have been growing demands for efficacious drugs to cure these resistant infections. The key mechanism for resistance to β-lactam antibiotics is the production of β-lactamases, which hydrolyze and deactivate β-lactams. Diazabicyclooctane (DBO) analogs play an important role as one of the new classes of β-lactamase inhibitors (BLIs), and several compounds such as avibactam (AVI) have been approved by the FDA, along with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…To access the sulfide derivatives, commercially available carboxylic acid 17 was subjected to a photo-induced Barton decarboxylative thiolation reaction with appropriate thiolating agents in the presence of 2-mercaptopyridine-1-oxide and ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC . HCl) [69,70] ANT3310: ANT3310 is the derivative of avibactam in which the carboxamide group of avibactam has been replaced with fluorine atoms (Scheme 4). This compound has been useful in restoring the carbapenem activity against OXA-CRAB as well as other SBLcarrying carbapenem-resistant Acinetobacter baumannii strains in in vivo mouse infection models [68].…”
Section: Durlobactam Prodrugs Etx1317 and Etx0282mentioning
confidence: 99%
See 2 more Smart Citations
“…To access the sulfide derivatives, commercially available carboxylic acid 17 was subjected to a photo-induced Barton decarboxylative thiolation reaction with appropriate thiolating agents in the presence of 2-mercaptopyridine-1-oxide and ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC . HCl) [69,70] ANT3310: ANT3310 is the derivative of avibactam in which the carboxamide group of avibactam has been replaced with fluorine atoms (Scheme 4). This compound has been useful in restoring the carbapenem activity against OXA-CRAB as well as other SBLcarrying carbapenem-resistant Acinetobacter baumannii strains in in vivo mouse infection models [68].…”
Section: Durlobactam Prodrugs Etx1317 and Etx0282mentioning
confidence: 99%
“…To access the sulfide derivatives, commercially available carboxylic acid 17 was subjected to a photo-induced Barton decarboxylative thiolation reaction with appropriate thiolating agents in the presence of 2-mercaptopyridine-1-oxide and ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC . HCl) [69,70] Thio-substituted DBOs: Researchers from Shiniogi pharmaceuticals reported a series of thio-substituted DBO derivatives in which the C2 position of DBO was transformed into sulfide, which was then oxidized to sulfinates and sulfones. To access the sulfide derivatives, commercially available carboxylic acid 17 was subjected to a photo-induced Barton decarboxylative thiolation reaction with appropriate thiolating agents in the presence of 2mercaptopyridine-1-oxide and Ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC•HCl) [69,70] This research group also prepared thio-substituted DBOs in which the N-hydroxy position of DBO was activated with fluoroacetate derivatives instead of sulfonic acid.…”
Section: Durlobactam Prodrugs Etx1317 and Etx0282mentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that a thio-functional group, such as sulfone, sulfoxide, or sulfonamide, at the C2 position of DBO enhances the ability to restore antimicrobial activities of βlactam against pathogens producing various serine β-lactamases and expands structural tolerance for β-lactamase inhibition at the 6-position. 18 In designing oral agents, carboxylic acid ester prodrugs are preferred to sulfate esters because they have been a proven strategy for oral administration. Although we have already ascertained that replacing the sulfate at the 6-position with fluoroacetic acid maintains β-lactamase inhibition potential, they were unstable in serum and showed high clearance in rats.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We have recently reported the fundamental structure−activity relationship (SAR) of thio-functionalized DBOs. 18 The representative compounds and their profiles are summarized in Table 1. The sulfone and sulfoxide derivatives exhibited better inhibition against β-lactamases.…”
Section: ■ Introductionmentioning
confidence: 99%